Resilience and learning: A case study of the department for international development’s governance and transparency fund - Wilkinson, Edith (Cranfield University, 2019)
Resilience is often defined as the ability to withstand and recover from shocks, but it can also relate to the ability to renew, re-organise and develop. In the UK, the resilience concept has permeated the policy domain; in particular, the areas of civil contingency and international development have attempted to operationalise the concept. An example of this is the Department for International Development’s (DFID) Governance and Transparency Fund (GTF), initiated in 2008 as a one-off £130 million fund to promote resilience through good governance and learning. Its purpose was to help people make their voices heard in order to hold their governments to account. It aimed to achieve this by strengthening the wide range of groups that are able to empower and support citizens. Funding was allocated to 38 programmes around the world, linking 1000 local organisations in over 100 countries. Over and above the core purpose of enhancing capability, accountability and responsiveness in relation to national governance, the GTF had an inbuilt responsibility to ensure the resilience of its programmes, making sure that the experiences, lessons and learning of the 38 programmes were shared. It focused on change through participatory experimentation and learning-centred practices. As such, the GTF placed learning at its heart and promoted a notion of resilience based on experiential learning. This thesis undertakes a case study of resilience and learning within GTF, designed to investigate whether and how learning for resilience can occur within and between disparate organisations. The thesis considers inter- and intra-organisational learning in order to determine how lessons are captured, interpreted and shared and whether these lessons provide a basis for future resilience, taking the GTF as a case study. The literature review considers two scholarly fields of study. The first is related to resilience, which explores the fundamental importance of adaptation in interconnected environments, based on an emerging body of literature known as the ‘social ecological’ literature. This branch of enquiry describes the systemic study of interrelations across scales (which are understood as ‘natural’ levels of analysis where they can be defined spatially, geographically, ecologically, socially, or institutionally), referred to as ‘panarchy’. The second literature review relates to learning, more specifically to experiential learning theory (which considers learning processes as closely related to direct experience) and its impact on the design, implementation and evaluation of learning beyond the level of the individual. The aim of this review was to identify learning processes that are applicable at intra-organisational and inter-organisational level. This resulted in the identification of Winswold et al’s (2009) ‘cycle for adaptation’, which proposes ii Modes of Governance, which can be summarised as hierarchies, markets and networks, that shape learning processes. The literature also acknowledged that learning processes bear an evolutionary perspective. Lifecycle models are examined and their resonance with social ecological adaptive cycles is highlighted. The dynamics presented in lifecycle models are offered to map innovation and learning within the aid and development sector. Both sets of models were then employed as an analytical framework, which was used in the design of the case study to guide the gathering, organisation and analysis of evidence. GTF was designed to empower and support citizens by ‘demanding accountability from the bottom up’. The GTF placed learning at its heart and promoted a notion of resilience based on experiential learning. Thus, the case study of GTF appears pertinent as it provides evidence and adds to the intersection of both areas of literature. The case study of GTF comprised three main research methods: content analysis and ethnographical analysis, followed by a series of semi-structured interviews. The investigation of GTF learning was approached in a systemic way by exploring each level of analysis (macro, meso and micro) to determine whether a dominant mode of governance had emerged and influenced learning. The conclusion of this study comes in the form of an answer to the question at its core which was: how does learning for resilience occur within and between disparate organisations of the aid and development sector? In combining elements of resilience and learning literatures a conceptual framework to understand ‘learning for resilience’ emerged and definition was coined. The case study showed that in a complex and multi-layered system, such as that represented by the GTF, learning takes place in a variety of ways and is undertaken by various actors. Manifestations of all three Modes of Governance (hierarchies, markets and network) were identified. For example, the overwhelming use of logframes is indicative of hierarchical modes of governance; financial considerations (including Value for Money), which were used as key success indicators, are indicative of market forces at play; and the promotion of networks was explicitly endorsed by all stakeholders in the GTF. When mapping the research findings against the phases of a typical lifecycle, learning dynamics appear complex; yet, drivers for learning at sector level as well as organisational level can be better understood. A Lifecycle Learning Model is drawn up which outlines the interplay between levels and demonstrates how strategies or trends at a given level resonate in another and ultimately provide insights on learning for resilience in the aid and development sector.